2020
DOI: 10.1002/cbm.2182
|View full text |Cite
|
Sign up to set email alerts
|

Life on parole: The quality of experiences soon after release contributes to a conviction‐free re‐entry

Abstract: Background: People returning to the community after prison face many challenges, including finding suitable accommodation and employment, and accessing good social support. The prospects are particularly poor for high-risk offenders with up to a third of those released in New Zealand returning to prison within 100 days. Aims/hypotheses: We developed the Parole Experiences Measure (PEM) to quantify the quality of men's life experiences during the first weeks of re-entry from prison. We aimed to answer the quest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…For example, the quality of pre-release planning is predictive of short-term recidivism outcomes (Dickson et al, 2013; Willis & Grace, 2008). More recently, research with the archive used in this study has shown that 2 months after release, the quality of the external circumstances in which parolees were living (e.g., levels and types of personal and community support, accommodation, employment), and to a lesser extent subjective wellbeing—recent mental and physical health, emotional experiences—were better in those who were free of convictions at 12 months post-release (Gwynne et al, 2020). Both successful external and internal circumstances (subjective wellbeing) are likely to be dependent on the ability to solve re-entry problems, which for most people will be aided with access to the emotional and practical resources of other people.…”
Section: Community Reintegration Processes and Tripm Psychopathy Comp...mentioning
confidence: 95%
See 3 more Smart Citations
“…For example, the quality of pre-release planning is predictive of short-term recidivism outcomes (Dickson et al, 2013; Willis & Grace, 2008). More recently, research with the archive used in this study has shown that 2 months after release, the quality of the external circumstances in which parolees were living (e.g., levels and types of personal and community support, accommodation, employment), and to a lesser extent subjective wellbeing—recent mental and physical health, emotional experiences—were better in those who were free of convictions at 12 months post-release (Gwynne et al, 2020). Both successful external and internal circumstances (subjective wellbeing) are likely to be dependent on the ability to solve re-entry problems, which for most people will be aided with access to the emotional and practical resources of other people.…”
Section: Community Reintegration Processes and Tripm Psychopathy Comp...mentioning
confidence: 95%
“…Because raw PEM item scores used several different metrics, items were standardized for all analyses, and then averaged for each scale. For descriptive statistics for each item and scale prior to standardization, see Gwynne et al (2020).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…One of the most intimidating challenges during reentry and exiting from crime is maintaining employment (Lukies et al, 2011; Sampson & Laub, 2003). Without stable employment, it is hard to achieve financial independence (Rydberg, 2018; Sampson & Laub, 2003) and establish structured daily routines (Gwynne et al, 2020; Osgood & Anderson, 2004), which are proven catalysts to desistance (Uggen & Kruttschnitt, 1998; Williams et al, 2019). Several factors have been proposed to explain why returning citizens encounter difficulty securing stable employment, ranging from employers’ reluctance to hire job applicants with criminal records (Holzer et al, 2002; Western & Sirois, 2019) to returning individuals’ low levels of education, limited vocational skills, and poor work histories (Fahey et al, 2006; Pager & Western, 2009).…”
Section: Introductionmentioning
confidence: 99%